2008
DOI: 10.1099/vir.0.2008/003897-0
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the ERK signal transduction pathway by Epstein–Barr virus immediate-early protein Rta

Abstract: BRCA1-associated protein 2 (BRAP2) is known to interact with the kinase suppressor of Ras 1 (KSR1), inhibiting the ERK signal transduction cascade. This study found that an Epstein-Barr virus (EBV) immediate-early protein, Rta, is a binding partner of BRAP2 in yeast and confirmed the binding in vitro by a glutathione S-transferase pull-down assay and in vivo by coimmunoprecipitation in 293(maxi-EBV) cells. Binding studies also showed that Rta and KSR1 interacted with the C-terminal 202 aa region in BRAP2. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…Since ERK signaling crucially influences autophagy (52) and Rta is known to transactivate the transcription of the Zta gene through ERK signaling (21), this study examined whether Rta affects autophagy through the ERK pathway. As expected, immunoblotting with phospho-specific ERK antibody revealed that the expression of Rta activated ERK activity and the phosphorylation of ERK induced by Rta was prevented by the presence of U0126, an inhibitor of MEK (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since ERK signaling crucially influences autophagy (52) and Rta is known to transactivate the transcription of the Zta gene through ERK signaling (21), this study examined whether Rta affects autophagy through the ERK pathway. As expected, immunoblotting with phospho-specific ERK antibody revealed that the expression of Rta activated ERK activity and the phosphorylation of ERK induced by Rta was prevented by the presence of U0126, an inhibitor of MEK (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Rta forms a complex with Sp1 through an adaptor protein, MCAF1, to autoregulate the transcription of its own gene (17,18). It also activates the transcription of the Zta gene, BZLF1, by activating phosphatidylinositol 3-kinase and mitogen-activated protein kinase pathways (19)(20)(21). Additionally, Rta induces cell cycle arrest in the G 1 phase and initiates a cellular senescence program in epithelial cells (22).…”
mentioning
confidence: 99%
“…These two proteins are activators of viral and cellular gene expression, play essential roles in lytic viral DNA replication, and impinge on many host cell processes, such as signal transduction, cell cycle control, and cellular senescence (10,27,30,31). The bzlf1 and brlf1 genes are not expressed during latency, but all external stimuli known to activate the EBV lytic cascade induce their expression (3,16,28,39,48).…”
mentioning
confidence: 99%
“…BZLF1 activates p38 and JNK to turn on the ATF2 transcription factor (22). BRLF1, another EBV immediate early protein, activates the AP-1 pathway by increasing the levels of phosphorylated p38, JNK, and ERK (22,23) and induces phosphorylation of Akt through the PI3K pathway (24). Activation of Akt, ERK, and p38 signaling is required for EBV reactivation from latency (25)(26)(27)(28).…”
mentioning
confidence: 99%